19-05: The clinical utility of real time, X-MRI guided left ventricular lead implantation for delivery of cardiac resynchronisation therapy. (10th June 2016) - Behar, Jonathan; Toth, Daniel; Remil, Sabrina; Panayiotou, Maria; Claridge, Simon; Jackson, Tom; Sohal, Manav; O'Neill, Mark; Brost, Alexander; Mountney, Peter; Razavi, Reza; Rhode, Kawal; et al.
Abstract: Purpose: Suboptimal LV lead placement contributes to cardiac resynchronization therapy (CRT) non-response. Cardiac MR (CMR) identifying myocardial scar & dyssynchrony allows targeted LV lead placement. Currently CMR is performed prior & separate to implantation. We describe a novel guidance platform, integrated within an XMR facility enabling CMR data acquisition, processing & analysis with immediate overlay onto live fluoroscopy. Methods & Results: Short & long axis cines & late gadolinium sequences are segmented and projected onto a 16-segment AHA model demonstrating location, transmurality & burden of myocardial fibrosis. Regional motion analysis demonstrates the latest mechanical activating segments. This process is performed seamlessly while the patient is within the XMR suite allowing segmented LV geometry/scar to be immediately co-registered with fluoroscopy. CS venography is overlaid onto the 3D-shell to identify the preferential targets for LV stimulation. This platform has been successfully used in 6 patients with no significant increase in procedure time or radiation dose compared with our historical controls (89 ± 18 vs. 113 ± 28 minutes & 826 ± 191 vs. 950 ± 450 cGycm2, p = ns). Late, target segments avoiding scar were paced in all cases. Visualization of the target informed positioning of the LV lead and enabled identification of the optimal poles to use for biventricular stimulation (Figure). Conclusion: Performing and processing CMR data in real time is feasible and may aid optimal LV lead placement for CRT delivery. This can be accomplished in a single sitting with no delay between CMR and CRT implant.